2016
DOI: 10.1016/j.canlet.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of angiogenic switch, cachexia and inflammation factors at the crossroad in undifferentiated thyroid carcinoma with BRAF

Abstract: Cachexia is the result of complex metabolic alterations which causes morbidity in patients with advanced cancers including undifferentiated (anaplastic) thyroid carcinoma (ATC). ATC is a lethal disease with limited therapeutic options and unclear etiology for cachexia. We hypothesize that the BRAFV600E oncoprotein triggers microvascular endothelial cell tubule formation (in vitro angiogenesis) by means of factors which play a crucial role in angiogenic switch, inflammation/immune response and cachexia. We use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…BRAF V600E could also be responsible for some clinical symptoms: in ATC the production and secretion of different angiogenic and pro-inflammatory key-factors (e.g. VEGFA, VEGFC, IL6) may contribute to the worsening of pathological features such as cachexia (the result of complex metabolic alterations which cause morbidity) 36 . Overall, these results highlight the complexity of tumor interaction with the microenvironment, and how this interplay can affect thyroid cancer progression and consequently patient prognosis.…”
Section: Genetic Alterations In Early Thyroid Tumorigenesismentioning
confidence: 99%
“…BRAF V600E could also be responsible for some clinical symptoms: in ATC the production and secretion of different angiogenic and pro-inflammatory key-factors (e.g. VEGFA, VEGFC, IL6) may contribute to the worsening of pathological features such as cachexia (the result of complex metabolic alterations which cause morbidity) 36 . Overall, these results highlight the complexity of tumor interaction with the microenvironment, and how this interplay can affect thyroid cancer progression and consequently patient prognosis.…”
Section: Genetic Alterations In Early Thyroid Tumorigenesismentioning
confidence: 99%
“…The mTORC1, which is a major signaling intermediary to stimulate anabolic processes, promotes skeletal muscle growth by increasing the adipogenesis and lipogenesis [ 53 ], and therefore inhibiting mTOR contributes to tumor cachexia. Cachexia is a result of complex metabolic alterations and causes morbidity and mortality in patients with advanced cancers such as undifferentiated (anaplastic) thyroid carcinoma [ 54 ]. It has been recently shown that the severe COVID-19 patients show cachexia like conditions but need more data to make conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The most common AEs included rash, fatigue, weight loss, anorexia, dysgeusia, and alopecia [ 76 , 77 ]. Preclinical studies showed that Vemurafenib downregulates angiogenic/cachectic and pro-inflammatory/immune response factors (IL-6, VEGFA, and VEGFC) that mediate microenvironment interactions between endothelial and ATC cells, thus inhibiting in vitro angiogenesis and lymphangiogenesis in ATC cells cultures [ 78 ]. Vemurafenib demonstrated also to be able to reduce ATC xenografts and metastasis growth in mice models [ 79 ].…”
Section: Main Textmentioning
confidence: 99%